2014
DOI: 10.1016/j.ijms.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Development of an analysis method of minor uranium isotope ratio measurements using electron multipliers in Thermal Ionization Mass Spectrometry

Abstract: a b s t r a c tA simple analytical procedure was developed to measure with high accuracy the isotope ratio of minor isotope of natural uranium present in small quantities using a thermal ionization mass spectrometer (TIMS). The reduction of quantities used for analysis and the measurement of non-abundant isotopes are of prime interest in the nuclear industry. Indeed it is necessary to reduce the analyst received dose and the effluent released, as well as realizing measurement at trace level. The new generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(50 citation statements)
references
References 21 publications
2
47
1
Order By: Relevance
“…The method employed in this study was previously described and was transposed to zirconium [21]. "Peak center" (mass calibration and ion beam centering in the detector) and lenses optimization were realized using the major zirconium isotope: 90 Zr + for the SPEX solutions isotope determinations and the nuclear samples concentration determinations or 91 Zr + for the enriched 91 Zr spike solutions isotope and concentration determinations.…”
Section: Total Evaporation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method employed in this study was previously described and was transposed to zirconium [21]. "Peak center" (mass calibration and ion beam centering in the detector) and lenses optimization were realized using the major zirconium isotope: 90 Zr + for the SPEX solutions isotope determinations and the nuclear samples concentration determinations or 91 Zr + for the enriched 91 Zr spike solutions isotope and concentration determinations.…”
Section: Total Evaporation Methodsmentioning
confidence: 99%
“…Several studies for zirconium isotope measurement have been reported in literature. They are mainly two principal techniques used for this kind of measurement: multiple collector-inductively coupled plasma mass spectrometer [2][3][4]9,10] (MC-ICP-MS) and thermal ionization mass spectrometry [1,2,5,6,8,[18][19][20] (TIMS). TIMS is a reference technique for isotope measurement [21][22][23]. TIMS allows reaching isotope ratio with high measurement trueness and precision.…”
Section: Introductionmentioning
confidence: 99%
“…There have also been different opinions on the influence of sample amount. Suzuki et al and Fujii et al separately reported that the sample amount had little influence on the measured rhenium and chromium isotopic ratios, whereas Foster et al found that the 11 B/ 10 B ratio decreased linearly with the sample amount and Quemet et al found that the 235 U/ 238 U ratio also decreased with the sample amount.…”
Section: Introductionmentioning
confidence: 99%
“…TIMS has been used for the detection of minor U isotopes by Quemet et al and they obtained less than 5% uncertainty for a 234 U/ 238 U isotope ratio with 50 ng samples using a peak jumping method with an electron multiplier. 78 They concluded that the use of a multi-ion counter (MIC) or SEM can improve the detection sensitivity, and decrease the analyzable quantity, from 1,270 ng for a Faraday cup-only case to 50 ng for cases of a Faraday cup with SEM, or a Faraday cup with MIC. Although ICP-MS is more commonly used in isotope analysis, TIMS remains one of the bestperforming mass spectrometers in a nuclear material analysis of environmental samples and nuclear forensics analysis.…”
Section: Mass Spectrometric Application In Nuclear Forensic Analysismentioning
confidence: 99%